2003
DOI: 10.1023/a:1025714412337
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: PEGylated adenoviruses are suitable gene delivery vehicles for oral administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In contrast, the SC-Ad vectors, can amplify antigen production during vaccination, but avoid the risk of adenovirus infection. They may particularly useful by the oral route, since most Ads are nearly quantitatively destroyed by stomach pH and digestive enzymes (Cheng et al, 2003). Therefore, RC-Ad4 and Ad7 vaccines were likely efficacious because they were able to amplify antigen production from the reduced number of cells that were infected by this stringent route.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the SC-Ad vectors, can amplify antigen production during vaccination, but avoid the risk of adenovirus infection. They may particularly useful by the oral route, since most Ads are nearly quantitatively destroyed by stomach pH and digestive enzymes (Cheng et al, 2003). Therefore, RC-Ad4 and Ad7 vaccines were likely efficacious because they were able to amplify antigen production from the reduced number of cells that were infected by this stringent route.…”
Section: Discussionmentioning
confidence: 99%
“…They went on to demonstrate that oral administration of the “stealth” PEGylated formulations to rats led to increased absorption of a poorly water soluble drug, danazol [160]. Cheng and coworkers PEGylated adenoviral vectors to improve their stability for oral administration as gene delivery vectors for colorectal cancer [161]. They covalently attached one of three different types of functionalized 5 kDa PEG to the free lysine groups on the protein capsids, and found that PEGylation with all three types of PEG actually increased the efficiency of transduction efficiency in differentiated enterocytes.…”
Section: Non-systemic Applications For Improved Delivery With Pegymentioning
confidence: 99%
“…They selected the vectors PEGylated with succinimidyl succinate functionalized PEG (SSPEG) for in vivo oral administration studies, finding significantly increased reporter protein expression throughout the GI tract (40-times higher expression in the colon) with the SSPEG vector compared to the unmodified adenoviral vector. Additional characterization of the internalization of SSPEG vectors by Caco-2 cells suggested that although they PEGylated 70-80% of the available attachment sites on the viral capsid, the PEGylation appeared to actually change the type of receptor interaction that led to internalization, which may have also led to increased gene transduction in vivo [161]. …”
Section: Non-systemic Applications For Improved Delivery With Pegymentioning
confidence: 99%
“…For example, crosslinking synthetic polymers onto the vector can reduce neutralization by anti-virus antibodies as well as enable evasion of innate immune responses, thereby enhancing gene transfer in the presence of existing antibodies and facilitating repeated administration by reducing subsequent adaptive immune responses to the vector (Kreppel and Kochanek, 2008). Polymeric materials that have been explored in conjunction with adenoviral and adeno-associated viral vectors have included polyethylene glycol (PEG; O’Riordan et al, 1999; Croyle et al, 2000, 2005; Cheng et al, 2003; De Geest et al, 2005; Eto et al, 2005; Lee et al, 2005; Mok et al, 2005; Oh et al, 2006; Hofherr et al, 2007), poly- N -(2-hydroxypropyl) methacrylamide (poly-HPMA; Fisher et al, 2001; Green et al, 2008), polysaccharides (Espenlaub et al, 2008), and others (Kasman et al, 2009; Kim et al, 2010). They are typically covalently conjugated through the reaction of active groups on the polymer termini to nucleophilic amino acid side chains on the viral surface, such as lysines and cysteines.…”
Section: Strategies To Avoid Neutralization By Humoral Anti-aav Immunmentioning
confidence: 99%